Pengaruh Penambahan Ekstrak Daun Mint (Mentha spp.) terhadap Karakteristik Fisik dan Organoleptik Lip Balm Berbasis Jambu Biji Merah (Psidium guajava L.) - Akbar Maulana Jonida; Miftahul Khair (MASALIQ, 2026)
Lip balm is a cosmetic product used to maintain moisture and protect the lips from dryness; therefore, the development of formulations using natural ingredients needs to consider the physical and organoleptic characteristics of the preparation. This study aimed to analyze the effect of adding mint leaf extract on the physical and organoleptic characteristics of lip balm based on red guava extract. The study employed an experimental method with three variations in mint leaf extract concentration, namely 2%, 4%, and 8%, while the concentration of red guava extract was maintained at 20%. The observed parameters included organoleptic characteristics, homogeneity, pH, melting point, and spreadability. The results showed that all formulations produced homogeneous preparations with a pink color and semisolid texture. Increasing the concentration of mint leaf extract produced an increasingly dominant mint aroma. All formulations had pH values ranging from 4 to 5, melting points of 50–55°C, and good spreadability. This study showed that the addition of mint leaf extract at concentrations of up to 8% could produce red guava extract-based lip balm with good physical and organoleptic characteristics. These findings provide practical implications for the development of natural ingredient-based lip balm formulations by considering the concentration of mint leaf extract as one of the components influencing the characteristics of the preparation.